Effect of post-polymerization heat treatments on the cytotoxicity of two denture base acrylic resins (Journal of Applied Oral Science, 2006)
INTRODUCTION: Most denture base acrylic resins have polymethylmethacrylate in their composition. Several authors have discussed the polymerization process involved in converting monomer into polymer because adequate polymerization is a crucial factor in optimizing the physical properties and biocompatibility of denture base acrylic resins. To ensure the safety of these materials, in vitro cytotoxicity assays have been developed as preliminary screening tests to evaluate material biocompatibility. ³H-thymidine incorporation test, which measures the number of cells synthesizing DNA, is one of the biological assays suggested for cytotoxicity testing. AIM: The purpose of this study was to investigate, using ³H-thymidine incorporation test, the effect of microwave and water-bath post-polymerization heat treatments on the cytotoxicity of two denture base acrylic resins. MATERIALS AND METHODS: Nine disc-shaped specimens (10 x 1 mm) of each denture base resin (Lucitone 550 and QC 20) were prepared according to the manufacturers' recommendations and stored in distilled water at 37ºC for 48 h. The specimens were assigned to 3 groups: 1) post-polymerization in a microwave oven for 3 min at 500 W; 2) post-polymerization in water-bath at 55º C for 60 min; and 3) without post-polymerization. For preparation of eluates, 3 discs were placed into a sterile glass vial with 9 mL of Eagle's medium and incubated at 37ºC for 24 h. The cytotoxic effect of the eluates was evaluated by ³H-thymidine incorporation. RESULTS: The results showed that the components leached from the resins were cytotoxic to L929 cells, except for the specimens heat treated in water bath (p